Lives of the English saints - Newman, John Henry (James Toovey, 1844)
[v.1] St. Augustine of Canterbury. -- [v.2] St. Ninian, bishop of Candida Casa. St. German, bishop of Auxerre. -- [v.3] Hermit saints: St. Gundleus, St. Helier, St. Herbert, St. Edelwald, St. Bettelin, St. Neot, St. Bartholomew, St. Paulinus, St. Edwin, St. Ethelburga, St. Oswald, St. Oswin, St. Ebba, St. Adamnan, St. Bega. -- [v.4] St. Wilfrid, bishop of York. Family of St. Richard, the Saxon: St. Richard, king; St. Willibald, bishop; St. Walburga, virgin, abbess; St. Winibald, abbot. -- [v.5] St. Wulstan, bishop of Worcester. St. Stephen, abbot. St. Gilbert, prior of Sempringham. -- [v.6] St. Aelred, abbot of Rievaux. St. William, archbishop of York. St. Waltheof; St. Robert. -- [v.7] St. Richard, bishop of Chichester. Stephen Langton, archbishop of Canterbury. St. Edmund, archbishop of Canterbury.